1998
DOI: 10.1093/ptj/78.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Stimulation on Edema Formation in Different Strains of Rats

Abstract: The finding that two of the three strains of rats responded to ES suggests that some strains of rats may be suitable models for the study of edema. That frogs and rats respond to high-voltage pulsed current suggests that humans might respond similarly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…These results agree with previous animal studies 7,8,10,11,25,27 that showed the effectiveness of HVPC(-) in the treatment of posttraumatic edema.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results agree with previous animal studies 7,8,10,11,25,27 that showed the effectiveness of HVPC(-) in the treatment of posttraumatic edema.…”
Section: Discussionsupporting
confidence: 93%
“…Negative polarity was more effective in most analyzed studies 8,10,11,25,27,28 , unlike a study that selected the anode as the active electrode 14 . This effect was also observed in the present study, in which the HVPC(-) group showed a higher percentage of reduction in edema and also a greater probability of reaching the end of treatment sooner.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…6 To confirm that limb-volume changes were caused by edema formation and not frank bleeding, investigators either made skin incisions on the involved limb just before the animal's sacrifice (frogs and rats) 6,13,14,[16][17][18][19]21 or viewed the injury through the animal's translucent skin (rats). 22 If it was determined that a subject suffered a more significant injury, investigators excluded the subject from data analysis. Two studies 15,20 did not mention any confirmatory procedures.…”
Section: Methods Of Trauma Inductionmentioning
confidence: 99%